Analysis of quantitative and qualitative parameters of youth entrepreneurship development in Kazakhstan - Zhartay, Zh.M. (BUKETOV BUSINESS REVIEW, 2019)
The article deals with the quantitative and qualitative parameters of the development of youth entrepreneurship in Kazakhstan. On the basis of analysis identified by such development as the number economicist active population of the Republic of Kazakhstan at the age of 15–28 years of their growth dynamics, the ratio of the economically active population of the Republic of Kazakhstan at the age of 15–28 years over the 2001–2018 with a total labor force of the country, the number of the economically active population of the Republic of Kazakhstan at the age of 15–28 years for 2001–2018, by region, by area, by kinds of economic activities, disaggregated by sex, by level of education. Also, the level of youth unemployment and its relationship with the youth category NEET. The implementation of the common efforts of the state, business, civil society institutions (NGOs) will contribute to the development of youth entrepreneurship is substantiated.